Immobilized Tannin from Sanseviera trifasciata on Carbon as Adsorbent For Iron(II) in Polluted Water Source - Irfan Hanafi Arif; Barlah Rumhayati; Masruri MASRURI (The Journal of Pure and Applied Chemistry Research, 2016)
The organic-agricultural waste resulted from local farmer or community gardening recently paid public attention. The presence and easily grown of “Lidah Mertua” or Sanseviera trifasciata being focused on potency investigation for its prospecting application. It was reported contain some phenolic and also tannin extracted from aqueous solvents. This paper revealed recent investigation applying of its isolated tannin from leave part to modifying of activated carbon. The previous report published that carbon were able to adsorb some toxic heavy metals. However, it has some limitation including lower capacity adsorption. Impregnated or immobilized the tannin-isolated from S. trifasciata leaves was able to modify the carbon functionality, physical appearance, pores size, and it adsorption capacity. Both Langmuir and Freundlich adsorption mechanism model also disclosed the developed adsorbent mechanism of iron(II) adsorption on the adsorbent tannin-immobolized on carbon. The real test using community well drilling water source also gave important finding on the concentration of iron(II) contained on water source.